Metamaterial‐inspired tri‐band antenna for 5G‐C and Ka band applications. Issue 9 (2nd June 2021) - Ruchi, Ruchi; Kartikeyan, Machavaram V.
Abstract: This article presents a novel tri‐band antenna design inspired by metamaterials for 5G‐C and Ka bands. The design employs an inverted U‐structured patch, a rectangular patch with E‐shape slot and a circular monopole loaded with complementary split ring resonator to achieve three operating bands with reduced overall antenna dimensions. It operates at 4.7 GHz (n79 band) in C‐band with maximum measured gain of 2.5 dB and two‐mm wave Ka bands at 28 GHz (n260 band) and 39 GHz (n261 band) with corresponding gain of 7.06 and 6.76 dB. The overall dimension of the proposed tri‐band antenna is 30 × 22 × 0.543 mm 3 and the bandwidths measured are 9.04%, 14.14%, and 2.46% at 4.7 GHz, 28 GHz, and 39 GHz, respectively. The experimented results are close to simulated ones.